Temporal/locative inversion in Arabic - Jarrah, Marwan (Yearbook of the Poznan Linguistic Meeting, 2017)
This research scrutinizes the observation that when the thematic subject is extracted (i.e. questioned) in Jordanian Arabic, temporal/locative inversion may occur. Temporal inversion occurs irrespective of the verb being transitive or intransitive, whereas locative inversion is limited to contexts with an unaccusative verb. This research argues that this distinction correlates with the base-generation of temporal/locative adjuncts; temporal adjuncts are base-generated adjoining to TP, whereas locatives are base-generated adjoining to VP. Temporal but not locative adjuncts resist fronting with vP, demand the use of a tense copula (or a tensed verb), and are not subject to deletion along with the lexical verb. With the assumption that Spec, SubjP must be filled with a non-silent copy due to the effects of the so-called Subject Criterion (Rizzi and Shlonsky 2007), a temporal or locative adjunct, if any, fills this position instead of the extracted thematic subject. Given its low position, a locative adjunct is accessible to Subj0 only when there is no v*P, hence the account of the correlation between locative inversion and the type of the verb. Furthermore, this research explores the existence of temporal/locative inversion in other two Arabic dialects (Najdi Arabic and Iraqi Arabic), arguing for a micro-parametric view of this strategy across Arabic dialects.